The measurement of sport sevice quality for unicipalities as local goverment units (Konya case) - Hayri Demır; Yusuf Barsbuga (Türk Spor ve Egzersiz Dergisi)
The aim of this study was to determine sport activity services municipalities carry out as local management units, consider viewpoints of people benefiting from these services and evaluate them as well. The participants of the study consist of 300 persons in total, including 90 persons from the center of fine arts included in the Meram District Municipality of Konya, 94 persons utilizing the Ertuğrul Gazi Recreational Facility in the Meram District Municipality of Konya and 115 persons from the center of vocational course in the Karatay District Municipality of Konya. In our study, the Service Quality Assessment Scale developed by Lam, Turkish reliability and acceptability done by Gürbüz, was performed. The One-Sample Kolmogorov-Smirnov test examined whether the data showed normal distribution, and it was made clear that the data displayed normal distribution. Since the data appeared to be normally-distributed, the Independent-Sample T test and the ANOVA test were also used for determining differences between the independent variables. As a result of our study; it was observed that there was no difference when the satisfaction levels of members were considered in the travel time, the marital status and the education level within the sub-dimensions of staff, program, facility and changing rooms in consequence of comparing the service quality expected and perceived from the members participating in the research. But the satisfaction level decreased when the membership duration, the usage frequency and the income level increased. Also, it was determined that the satisfaction levels of participants who had individual membership type and were over the age of 18, were higher than ones having family membership type and aged under 18. As a result of our study; it was observed that the expected and perceived service quality satisfaction approaches of participant members, effected from membership type, membership period, frequence of facility usage and ages of members.